2015
DOI: 10.1177/0143034315604018
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional longitudinal associations of perpetration and victimization of peer bullying with psychosocial problems in adolescents: A cross-lagged panel study

Abstract: Research on school bullying often focuses on the directional path of bullying and/or victimization leading to psychosocial problems, while such one-dimensional views have been shown to be too simplistic. Furthermore, recent research has shown that patterns of bullying at school differ for boys and girls, which makes gender a particularly relevant factor in exploring the causes and consequences of bullying. Therefore, the present study explored the bidirectional, longitudinal associations of bullying and bullyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 48 publications
2
25
1
3
Order By: Relevance
“…Most longitudinal studies have examined the impact of victimization on depression (Sweeting, Young, West, & Der, ; Takizawa, Maughan, & Arseneault, ; Zwierzynska, Wolke, & Lereya, ), while others have examined the impact of depression on becoming victimized (Tran, Cole, & Weiss, ). A few longitudinal studies have examined the bidirectional association between victimization and depression, generally indicating that there is a bidirectional association between the two (Busch, Laninga‐Wijnen, van Yperen, Schrijvers, & De Leeuw, ; Lester, Cross, Dooley, & Shaw, ; Reijntjes, Kamphuis, Prinzie, & Telch, ; Tran et al., ) which may be different among genders (McMahon, Reulbach, Corcoran et al., ; McMahon, Reulbach, Keeley, Perry, & Arensman, ; Sentse, Prinzie, & Salmivalli, ; Tran et al., ). These studies indicate that depression both precedes and follows victimization.…”
Section: Introductionmentioning
confidence: 99%
“…Most longitudinal studies have examined the impact of victimization on depression (Sweeting, Young, West, & Der, ; Takizawa, Maughan, & Arseneault, ; Zwierzynska, Wolke, & Lereya, ), while others have examined the impact of depression on becoming victimized (Tran, Cole, & Weiss, ). A few longitudinal studies have examined the bidirectional association between victimization and depression, generally indicating that there is a bidirectional association between the two (Busch, Laninga‐Wijnen, van Yperen, Schrijvers, & De Leeuw, ; Lester, Cross, Dooley, & Shaw, ; Reijntjes, Kamphuis, Prinzie, & Telch, ; Tran et al., ) which may be different among genders (McMahon, Reulbach, Corcoran et al., ; McMahon, Reulbach, Keeley, Perry, & Arensman, ; Sentse, Prinzie, & Salmivalli, ; Tran et al., ). These studies indicate that depression both precedes and follows victimization.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for the continuation of internalizing problems in escaped victims is the idea that early stressful experiences can set an individual on a depressed trajectory from which they may not be able to deviate, due to the tendency for a depressed person to withdraw from potentially beneficial social support systems (Petersen, ). A bidirectional relationship between victimization and psychological outcomes may also be to blame—depression and loneliness are not just consequences of being bullied, but are characteristics that often contribute to one's victim status (Busch, Laninga‐Wijnen, van Yperen, Schrijvers, & De Leeuw, ). Similarly, Park, Jensen‐Campbell, and Miller (in press) found that peer victims develop an overall lower threshold for social pain; i.e., peer victims report higher threatened self‐esteem, belongingness, meaningful existence, and control across a wider spectrum of social situations—even in those where they are obviously included and accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Разлози за овакво понашање објашњени су дифузијом одговорности или специфичностима процене насилног понашања од стране посматрача (Salmivalli, 2010), а резултати истраживања медијског дискурса показују да је чак и у медијима највише деце представљено кроз улогу посматрача (Torlak, 2016), упркос последицама које вршњачко понашање може да има и по насилника и по жртву у даљој временској перспективи (нпр. Arseneault et al, 2010;Busch et al, 2015;Kim et al, 2011). Ипак, у највећем броју истраживања више пажње се посвећује насилницима и жртвама управо због њихове "активне" улоге у насилној интеракцији и последица насиља по њихову социјалну адаптацију у каc-нијем развоју.…”
Section: школско насилништво и виктимизација: дефинисање концепта и уunclassified